Investigation of heavy metal and radionuclide distribution in silt of lake Didžiulis - Butkus, Donatas; Šalčiūnienė, Kristina (Journal of Environmental Engineering and Landscape Management, 2011)
The article deals with research of the ecological situation in Lake Didžiulis, located nearby the highway Vilnius–Kaunas (Trakai District); the most polluted locations in the lake were identified. Research of heavy metals (HM) and radionuclides in the lake silt is described. To research HM concentrations and the specific activities of radionuclides, the samples were collected from 12 bores in the most typical locations of the lake. The estimated HM concentrations in the silt of Lake Didžiulis vary within a wide range: Cr from 6.9 to 45.2 mg/kg, Ni from 20.4 to 55.7 mg/kg, Mn from 236 to 1362 mg/kg, Cu from 7.1 to 80.9 mg/kg, Pb from 24.4 to 87.8 mg/kg, Zn from 13.0 to 75.8 mg/kg. The HM concentrations in the lake silt do not exceed the maximum allowed concentrations (MAC) in the soil, whereas the concentrations of manganese, copper and lead in some samples are close to MAC. The counted specific activities of 40K fluctuate from 46 Bq/kg to 415 Bq/kg in the upper level silt and from 125 Bq/kg to 482 Bq/kg in the silt, which is found near the mineral soil. The specific activities of other radionuclides at the said depths of the silt range as follows: 226Ra from 23 Bq/kg to 85 Bq/kg and from 28 Bq/kg to 93 Bq/kg, 227Ac from 2.1 Bq/kg to17.0 Bq/kg and from 7.3 Bq/kg to 23.0 Bq/kg, whereas artificial 137Cs from